2014
DOI: 10.21273/jashs.139.6.657
|View full text |Cite
|
Sign up to set email alerts
|

Amplified Fragment Length Polymorphism Fingerprinting to Identify Genetic Relatedness among Lychee Cultivars and Markers Associated with Small-seeded Cultivars

Abstract: Amplified fragment length polymorphism (AFLP) was used to assess genetic relatedness among 23 popular commercial cultivars of lychee (Litchi chinensis) and identify the markers associated with small-seeded cultivars. A combination of three primer pairs with high discriminatory ability was selected for resolving the identity of lychee cultivars. The marker system resolved the instances of synonymies and homonymies. The two cultivars, Dehrarose and Dehradun, whose names are oft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 24 publications
3
5
0
Order By: Relevance
“…A Mantel test between genetic distance and morphological distance did not produce significant correlation (R 2 = 0.005, p < 0.85) (Supplementary Figure S3). The lack of correlation between these two different approaches agreed with the report of Pathak et al [102] in lychee cultivars, where they observed different identification results using molecular markers and morphological traits. A similar cluster pattern was also reported in the accession of S. italica by Dvorakova et al [98] and Sikdar et al [101], who used ISSR and RAPD markers, respectively.…”
Section: Resultssupporting
confidence: 90%
“…A Mantel test between genetic distance and morphological distance did not produce significant correlation (R 2 = 0.005, p < 0.85) (Supplementary Figure S3). The lack of correlation between these two different approaches agreed with the report of Pathak et al [102] in lychee cultivars, where they observed different identification results using molecular markers and morphological traits. A similar cluster pattern was also reported in the accession of S. italica by Dvorakova et al [98] and Sikdar et al [101], who used ISSR and RAPD markers, respectively.…”
Section: Resultssupporting
confidence: 90%
“…The distant accessions such as PM-01 and PM-15 identified on the basis of combined ISSR and RAPD markers were found to be identical in terms of bloom start, full bloom, and culm length, whereas genetically identical accessions (PM-14 and PM-15) differed in terms of plant height, leaf length, leaf width, ration of leaf length/width, culm length, stem diameter, and spike length and width. The lack of correlation between these two different approaches agreed with the report of Pathak et al [97] in lychee cultivars, where they observed different identification results using molecular markers and morphological traits. Meanwhile, others argued that variability among accessions may be caused by uncontrolled spread of plant materials and longtime sexual reproduction and different degrees of domestication causing regular expression of certain genes and inactivation of other genes [98].…”
Section: Discussionsupporting
confidence: 90%
“…Two litchi genotypes of contrasting seed size - Calcuttia (bold seeded) and Seedless Late (small seeded), were selected for the study. In our previous study, these two genotypes were reported to be closely genomically related, with the Nei 72 genetic distance of 0.3695. The hermaphrodite female flowers, with two lobed styles and sticky stigma, were identified on the panicle as highly receptive flower stage and marked as 0 DAA (days after anthesis).…”
Section: Methodsmentioning
confidence: 93%